Dynamic stability: Unfolding dynamics of vicious cycles in a design firm. Issue 1 (February 2022) - Lalaounis, Sotiris T.; Nayak, Ajit
Abstract: Paradoxes generate tensions and contradictions in organizations. In this paper, we contribute to the paradox literature by developing a complex systems approach to how organizational members experience tensions generated by the strategic intent paradox. Specifically, we focus on the unfolding dynamics of vicious cycles experienced by organizations dealing with paradox. Drawing on a case study of a design firm, we demonstrate how a vicious cycle forms through feedback loops and develops dynamic stability over time. On the basis of our findings, we develop a micro-level understanding of vicious cycles, which incorporates defence mechanisms at staff and senior management levels. Our main contribution is a theoretical model of unfolding dynamics of vicious cycles. Our model shows the importance of (1) feedback loops that underpin a vicious cycle and (2) importance of circular causality, reinforcing cycles, and micro-mechanisms in theorizing vicious cycles.